2014
DOI: 10.1093/ndt/gfu075
|View full text |Cite
|
Sign up to set email alerts
|

Gitelman syndrome and glomerular proteinuria: a link between loss of sodium-chloride cotransporter and podocyte dysfunction?

Abstract: We report on a 27-year-old patient presenting with chronic hypokalaemia, inappropriate kaliuresis, hypomagnesaemia and alkalosis, associated with moderate proteinuria. Genetic analysis evidenced a homozygous mutation ( p.Arg399Cys) in the SLC12A3 gene coding for the sodium-chloride cotransporter (NCC), confirming the diagnosis of Gitelman syndrome. Further genetic testing did not show any mutation in NPHS2. A renal biopsy was performed in view of the unusual association with proteinuria. Light microscopy showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…Isolated cases of focal segmental glomerulosclerosis (FSGS) and C1q nephropathy in Gitelman patients have been reported as well [ 14 , 15 ]. Devuyst also found that GS was related to glomerular proteinuria and abnormalities of the glomerular basement membrane (GBM) [ 16 ]; defects of the GBM and podocytes were also detected in the Slc12a3 knockout mouse model [ 17 ]. These studies suggest that the association between GS and secondary changes of the kidney is probably not coincidental.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated cases of focal segmental glomerulosclerosis (FSGS) and C1q nephropathy in Gitelman patients have been reported as well [ 14 , 15 ]. Devuyst also found that GS was related to glomerular proteinuria and abnormalities of the glomerular basement membrane (GBM) [ 16 ]; defects of the GBM and podocytes were also detected in the Slc12a3 knockout mouse model [ 17 ]. These studies suggest that the association between GS and secondary changes of the kidney is probably not coincidental.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Reports suggest that GS may be associated with glomerular proteinuria due to abnormalities of the glomerular basement membrane. 22,49 Chronic kidney disease might develop in GS patients due to either chronic hypokalemia, which is associated with tubulointerstitial nephritis, tubule vacuolization, and cystic changes, or volume depletion and increased reninangiotensin-aldosterone, which may contribute to renal damage and fibrosis. 21,50,51 Many patients with GS present with abdominal pain, which may be due to intestinal paresis because of hypokalemia or intolerability of potassium and magnesium supplementation.…”
Section: Clinical Manifestations and Workupmentioning
confidence: 99%
“…Several recent studies have reported that some subsets of patients tend to show overt proteinuria 29 , 30 ) , which has received attention as an independent risk factor for cardiovascular and chronic kidney disease 31 ) . Empirical evidence available in the literature shows several glomerulopathies and concomitant proteinuria in patients with GS 32 , 33 , 34 ) . A few reports have even anecdotally described patients with severe progressive renal failure requiring renal replacement therapy 35 , 36 ) .…”
Section: Discussionmentioning
confidence: 99%